2023
DOI: 10.3390/nano13182507
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneity of Needleless Electrospun Nanofiber Mats

Edona Morina,
Marius Dotter,
Christoph Döpke
et al.

Abstract: Nanofiber mats can be electrospun by different techniques, usually subdivided into needle-based and needleless. The latter allow for producing large-area nanofiber mats, e.g., with a width of 50 cm and lengths of several meters, if electrospinning proceeds for several hours, depending on the required thickness. Even spinning smaller samples, however, raises the question of homogeneity, especially if defined mechanical properties or a defined thickness is required, e.g., for filtration purposes. Very often, onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
(54 reference statements)
0
0
0
Order By: Relevance
“…The mass of each specimen was measured by an analytical balance VWR LA Classic (VWR International GmbH, Darmstadt, Germany). Even in the case of optically homogeneous nanofiber mats, a study has shown strong deviations in areal weight and thickness between neighboring segments [33], making it necessary to measure each single sample. To investigate the influence of the areal weight, thicker and thinner areas of the produced nanofiber mats were chosen, resulting in a broad range of areal weights of about 0.9 g/m 2 -13.9 g/m 2 .…”
Section: Electrospinningmentioning
confidence: 99%
“…The mass of each specimen was measured by an analytical balance VWR LA Classic (VWR International GmbH, Darmstadt, Germany). Even in the case of optically homogeneous nanofiber mats, a study has shown strong deviations in areal weight and thickness between neighboring segments [33], making it necessary to measure each single sample. To investigate the influence of the areal weight, thicker and thinner areas of the produced nanofiber mats were chosen, resulting in a broad range of areal weights of about 0.9 g/m 2 -13.9 g/m 2 .…”
Section: Electrospinningmentioning
confidence: 99%
“…The components of needle-free electrospinning are an upper wire, a lower wire, a carriage containing a polymer solution and a substrate for collecting the nanofibers, which are generated in a high-voltage field. The lower wire is coated with an electrospinning solution, Taylor cones are formed in the electrospinning process, and the resulting nanofibers are deposited onto a nonwoven substrate, such as polypropylene, located under the upper wire [14]. The needle-based electrospinning machine, on the other hand, consists of a pump, a syringe, a high-voltage power supply, a needle and a collector.…”
Section: Introductionmentioning
confidence: 99%